Regulation of Dichloroacetate Biotransformation in Rat Liver and Extrahepatic Tissues by GSTZ1 Expression and Chloride Concentration - Jahn, Stephan C. (Biochem Pharmacol, 2018)
Biotransformation of dichloroacetate (DCA) to glyoxylate by hepatic glutathione transferase zeta 1 (GSTZ1) is considered the principal determinant of the rate of plasma clearance of the drug. However, several other organismal and subcellular factors are also known to influence DCA metabolism. We utilized a female rat model to study these poorly understood processes. Rats aged 4 weeks (young) and 42 to 52 weeks (adult) were used to model children and adults, respectively. Hepatic chloride concentrations, which influence the rate of GSTZ1 inactivation by DCA, were lower in rat than in human tissues and rats did not show the age dependence previously seen in humans. We found GSTZ1 expression and activity in rat brain, heart, and kidney cell-free homogenates that were age-dependent. GSTZ1 expression in brain was higher in young rats than adult rats, whereas cardiac and renal GSTZ1 expression levels were higher in adult than young rats. GSTZ1 activity with DCA could not be measured accurately in kidney cell-free homogenates due to rapid depletion of glutathione by γ-glutamyl transpeptidase. Following oral administration of DCA, 100 mg/kg, to rats, GSTZ1 expression and activity were reduced in all rat tissues, but chloride concentrations were not affected. Together, these data extend our understanding of factors that determine the in vivo kinetics of DCA.